Outage probability analysis of RIS-assisted wireless networks with von mises phase errors - Wang, T; Badiu, MA; Chen, G; Coon, JP (IEEE, 2021)
In this paper, we investigate the performance of a communication link assisted by a reconfigurable intelligent surface (RIS) over line-of-sight (LOS) channels. The phase configuration of the RIS is imperfect and the phase error for each reflective element is modeled by a Von Mises distribution. First, we derive novel closed-form approximations for the lower tail distribution of the magnitude of the equivalent channel coefficient. Then, we use the obtained expressions to evaluate the outage probability and diversity order of the proposed system. Approximation errors of the proposed method are analyzed in detail. Simulation results validate the theoretical analysis is accurate at a high signal-to-noise ratio (SNR) regime.